Model of Sharia Bank Profitability Determination Factors by Measuring Internal and Externals Variables - Sihotang, Mutiah Khaira; Hasanah, Uswah; Hayati, Isra (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2022)
This study examines the influence of internal and external factors on profitability as proxied by Return on Assets (ROA), a study on Islamic Commercial Banks for the 2016-2020 period. In the theory of profitability, there are 2 factors that affect bank profitability, namely internal factors and external factors. Internal factors in this study are BOPO (Operating Expenses to Operating Income), Non-Performing Financing (NPF), Financial to Deposit Ratio (FDR) and external factors in this study are inflation and the money supply. Profitability is one of the most important factors in a company, including Islamic financial institutions, in this case Islamic banks, so that every company must pay attention to the company's profitability ratios. Islamic banks are financial institutions that just started to emerge in the late 90s and have a very high level of competition with conventional banks. For this reason, this study aims to look at the financial performance of Islamic banks in Indonesia through the level of profitability they have had for the last 5 years. The sample selection in this study used purposive sampling method. The sample in this study is the monthly financial statements of Islamic commercial banks in Indonesia in 2016-2020. The data in this study will be processed using SPSS software with multiple regression. The results of this study state that inflation as an external factor does not have a significant effect on the profitability of Islamic Commercial Banks as measured by the Return on Assets (ROA) ratio with a significance level of 0.628 and the money supply has a significant effect on ROA. While the BOPO, NPF and FDR variables as internal factors have a significant effect on ROA.